The Agricultural Adjustment Act and The Reports of the Brookings Institution - Garver, F. B.; Trelogan, Harry (Quarterly Journal of Economics, 1936)
I. Introduction, 594.— II. Conditions of supply of agricultural products, 595.— III. Emergency problems of agriculture, 596.— IV. Fundamental agricultural problems, 597.— V. The Agricultural Adjustment Act in relation to the problems, 600.— VI. Wheat, 601.— VII. Cotton, 603.— VIII. Livestock, 605.— IX. Dairy industry, 609.— X. Tobacco, 613.— XI. Marketing agreements, 615.— XII. Summary and conclusions, 617.